Characterization of head movement patterns in patients with bilateral and unilateral vestibulopathy during functional mobility tasks - Grouvel, Gautier; Corre, Julie; Ranieri, Maurizio; Cavuscens, Samuel; Boutabla, Anissa; Cugnot, Jean-François; van de Berg, Raymond; Guinand, Nils; Armand, Stéphane; Pérez Fornos, Angélica (Frontiers in Neuroscience, 2026)
IntroductionBilateral and unilateral vestibulopathies mainly cause chronic imbalance/unsteadiness and oscillopsia, significantly impacting quality of life. Traditional clinical tests fail to assess functional impact on daily activities. This study aimed to characterize head movement patterns in bilateral vestibulopathy (BV) and unilateral vestibulopathy (UV) patients during functional mobility tasks in a semi-standardized environment. This study could provide useful information for rehabilitation and optimization of vestibular implant stimulation.MethodsFifty-nine participants (19 BV, 20 UV, 20 healthy subjects) performed 10 functional mobility tasks, and a subtask extracted during analysis, while wearing inertial measurement units that recorded head angular velocities. Angular accelerations were derived from these. Vector norms and mode values of distribution histograms were calculated for both variables. Statistical analyses were performed using linear mixed-effects models to compare head movement parameters (angular velocity and angular acceleration) between groups (healthy subjects vs. patients) and tasks (walk vs. other tasks), including group × task interactions. Correlation analyses were also performed to compare the objective values with the patients’ perception of task difficulty.ResultsVestibulopathy patients demonstrated significantly reduced head movements compared to healthy subjects. BV patients showed the most restrictive patterns (angular velocities estimated between 8 and 12 deg/s; accelerations between 85 and 150 deg/s2, with statistically significant main effects of group and task and specific significant group × task interactions). UV patients exhibited intermediate values with greater variability. Healthy subjects displayed task-specific adaptations and higher movement ranges (Q1-Q3 area: 5.97 vs. 3.58 vs. 2.69 deg2/s3 (angular velocity x angular acceleration) for healthy, UV, and BV groups respectively).ConclusionVestibulopathy leads to compensatory head stiffening strategies specific to certain tasks, with BV patients exhibiting the most pronounced limitations. These findings may suggest that patients adopt cautious motor behaviors during their functional mobility activities. This ecological assessment provides essential parameters for optimizing vestibular rehabilitation protocols and defining realistic technical requirements for vestibular implants.